PENGARUH KEPEMIMPINAN VISIONER KEPALA MADRASAH TERHADAP KEPERCAYAAN ORANG TUA DAN MINAT MENYEKOLAHKAN ANAK KE MADRASAH (STUDI KUANTITATIF DI MDTA HIDAYATUL MUTA’ALLIMIN, CIREBON) - Sya’roni; Mulyadi; Dewi Cahyani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the influence of visionary leadership of the madrasah principal on parental trust and their interest in enrolling their children in the madrasah. The declining public interest in Madrasah Diniyah Takmiliyah (MDT) serves as the background of this research. A correlational quantitative approach was employed, using multiple linear regression analysis. The population comprised parents of students at MDTA Hidayatul Muta’allimin, Cirebon, with a purposive sample of 60 respondents. Data were collected through a Likert-scale questionnaire that had undergone validity and reliability testing. The results indicate that visionary leadership significantly influences parental trust (p < 0.05), and parental trust significantly affects parents’ interest in enrolling their children. Visionary leadership also has both direct and indirect effects on enrollment interest, mediated by trust. These findings support the theory of visionary leadership and highlight trust as a strategic factor in educational decision-making. The study recommends that Islamic educational institutions adopt communicative, transparent, and future-oriented leadership to increase parental interest and institutional credibility.